ANALISIS DAERAH RESAPAN DI DAERAH RAWAN BANJIR KABUPATEN BANJAR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Hapsari, Putri; Nurlina, Nurlina; Sota, Ibrahim (Jurnal Fisika FLUX, 2013)
Abstract: Floods not only cause flooded rice field so it cannot be harvested anddestroyed settlements, but also destroying social and economic services and publicinfrastructure, and even casualties. With so many problems that can lead to flooding andnot knowing suitability flood catchment areas, the study sites were taken in Banjar. Theparameters used for the analysis of catchment areas are flooded soil type, land cover,slope, spatial plans and topography, as well as the supporting data that maps hydrologyand flood vulnerability maps. These parameters are considered as a major factor indetermining the flood catchment areas. Results obtained from the analysis above thatmatching method is then mapped to a suitable area as a flood catchment areas locatedin five regions covering sub Aluh-Aluh, part of Gambut District, part of the District ofBeruntung Baru, part of the District Mataraman and part of the district Tatah Makmur.Keywords: Mapping, GIS, Matching Method, Regional Infiltration Flood, Banjar District